2020
DOI: 10.1515/ntrev-2020-0080
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-modified wool for adsorption of redox metals and potentially for nanoparticles

Abstract: Electron beam irradiated sheep wool with absorbed radiation doses ranging from 0 to 165 kGy showed good adsorption properties toward copper cations. The Cu(ii) being Lewis acid generated several types of complex salts based on carboxylates or cysteinates with ligands available in keratin. Under these conditions, cross-links were formed between the keratin chains. Experimental data obtained from Cu(ii) adsorption using the concentration of 800–5,000 mg/L were tested for fitting to 10 isotherm models. Various co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…All mentioned cations are complexforming. In the analysis of Co(II)'s fitting for 10 models of adsorption isotherms [53], agreements with the Langmuir, Flory-Huggins and Redlich-Peterson models were shown. When comparing the results with those of the models applied for Cr(III), it was found that none of the 10 models were adequate for both Cr(III) and Co(II).…”
Section: The Removal Of Other Species Using Woolmentioning
confidence: 74%
See 1 more Smart Citation
“…All mentioned cations are complexforming. In the analysis of Co(II)'s fitting for 10 models of adsorption isotherms [53], agreements with the Langmuir, Flory-Huggins and Redlich-Peterson models were shown. When comparing the results with those of the models applied for Cr(III), it was found that none of the 10 models were adequate for both Cr(III) and Co(II).…”
Section: The Removal Of Other Species Using Woolmentioning
confidence: 74%
“…The copper cation showed adherence to Langmuir, Flory-H and partially Redlich-Peterson models. The latter clearly distinguished the nati from the modified ones [53].…”
Section: The Removal Of Other Species Using Woolmentioning
confidence: 90%
“…Prewetting for 24 h compared to the corresponding non-prewetted sample after 1 h contact increased the sorptivity for 0 kGy by 55%, 48 kGy by 120%, and 153 kGy up to 170%. In the adsorption isotherm fitting test, chemisorption was confirmed in the case of Cu adsorption by applying the Flory-Huggins model [29]. In chemisorption, the Cu(II) cation reacts with the R-COOH groups on the keratin side chains (such as aspartic acid, glutamic acid, and cysteine) to form Cu-salts.…”
Section: Prewetted Sheep Woolmentioning
confidence: 99%
“…In the adsorption isotherm fitting test, chemisorption was confirmed in the case of Cu adsorption by applying the Flory-Huggins model [29]. In chemisorption, the Cu(II) cation reacts with the R-COOH groups on the keratin side chains (such as aspartic acid, glutamic acid, and cysteine) to form Cu-salts.…”
Section: Prewetted Sheep Woolmentioning
confidence: 99%
“…However, it was shown that the effect of irradiation is complex, and each dose may provoke different effects on the wool keratin structure [ 35 ]. Furthermore, several studies reported the improvement of the sorption affinity of wool keratin towards some metal cations and therefore its usefulness in environmental cleaning [ 36 , 37 , 38 , 39 , 40 ]. In a previous attempt to prepare biocompatible hair and wool keratins hydrogels via EBI, a blend with synthetic polymers was necessary to obtain a gel after irradiation [ 41 ].…”
Section: Introductionmentioning
confidence: 99%